2010
DOI: 10.1177/0018726709348938
|View full text |Cite
|
Sign up to set email alerts
|

New approaches to employee voice and participation in organizations

Abstract: While the history of employee voice and participation is longstanding, there has been a sharp increase in interest in these topics among academics, practitioners, and policy-makers in recent years. The research on employee voice and participation has therefore significantly broadened, expanding from an earlier institutional focus to also include significant behavioural and strategic streams. This article introduces a symposium that extends our knowledge of employee voice and participation in terms of new organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
126
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(128 citation statements)
references
References 15 publications
0
126
0
2
Order By: Relevance
“…However, employee voice can potentially also be in favour of the status quo and in support of existing organisational practices (Burris et al, 2012). Universally acceptable definitions of voice thus remain elusive, and the relationship with related terms such as participation remains blurred (Budd et al, 2010).…”
Section: Employee Voicementioning
confidence: 99%
“…However, employee voice can potentially also be in favour of the status quo and in support of existing organisational practices (Burris et al, 2012). Universally acceptable definitions of voice thus remain elusive, and the relationship with related terms such as participation remains blurred (Budd et al, 2010).…”
Section: Employee Voicementioning
confidence: 99%
“…Organizations also assign a specific department to address such issues as Human Resource (HR) department [19,38]. The nature and procedure of MEV is a two way communication, in which organizations provide different platforms (medium) and different forms of organizational social media connections where employees can raise their voice regarding issues and suggestions [39] to their supervisor or top management [40]. Supervisors and management are responsible to acknowledge the issues and provide solutions in a certain period of time.…”
Section: Modern Employee Voicementioning
confidence: 99%
“…Medium is one of the important elements for successful communication, and platform plays the role of the medium in MEV. Budd et al [39] suggested that organizations must provide a medium to conduct successful communication between their employees and management. For organizations which provide platform to employees to raise their voice, favourable outcomes have been witnessed such as decrease in absenteeism and increase in job performance and productivity.…”
Section: Communication Theorymentioning
confidence: 99%
“…According to Hirchman's perspective, voice can be described as an attempt to change, rather than escape from the issue. Voice as individual dissatisfaction perspective can be focused on a specific problem, but another perspective of voice can be the expression of a collective organization like union membership creates official voice to eliminate dissatisfaction (Budd, Paul, &Adrian, 2010;Dundon, Wilkinson, Marchington, & Ackers, 2004).…”
Section: Psychological Capital and Employee Voice As Mediatormentioning
confidence: 99%
“…Individual differences such as big five personality traits, self-esteem, and self-efficacy have been examined as predictors of voice (Budd et al, 2010). Top management support for openness, trust in supervisor cause willing to speak up (Landau, 2009).…”
Section: Psychological Capital and Employee Voice As Mediatormentioning
confidence: 99%